SELECTION AND JUSTIFICATION OF RUBBER, WHICH INCREASES THE PROTECTIVE PLASTICITY IN THE DESIGN OF SPECIAL CLOTHES (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2024)
In this article, the increasing protective properties of rubber used for special workwear in various industries are selected and justified.